The Factors Affect towards the Competitive Advantage of Tourism Services Business in Luang Prabang City, Luang Prabang Province In the case of Hotel-Resort Business - Phanthouamath, Poutthalack; Hoongsengpha, Soudtida; Indavong, Dalounny (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The objectives of this research were to 1) study the competitive advantage of tourism services business in Luang Prabang City and 2) to analysis the factors affect towards the competitive advantage of tourism services Business in Luang Prabang City, Luang Prabang Province, the research was conducted by using a questionnaire as an instrument for collecting data from 95 hotel and resort executives/Entrepreneurs in the Luang Prabang district of Luang Prabang Province. The Cronbach alpha reliability coefficient was 0.986, the statistics used for data analysis were frequency, percentage, mean, standard deviation, Multiple Regression analysis. The results revealed that: 1) the hotel-resort business in the Luang Prabang City was a competitive advantage at high level, in which the competitive advantage at a highest level, the first factor was the advantage in terms of quick response Leadership and the operation with a high level of competitive advantage in the first order was the aspect of focus/niche market, followed by the aspect of differentiation and the finally advantage was in terms of operating cost Leadership, and 2) the organization management strategic factors were affected toward on the competitive advantage of the hotel-resort business in Luang Prabang city include 2 factors: the operation system and management style factors; for the marketing factors were affected toward on the competitive advantage of the hotel-resort business in Luang Prabang city include 2 factors: personnel factor and physical characteristics factor; the result of these factors was the same direction.